Inflammatory fibroid polyp (Vanek’s polyp): a case report and literature review - Fazzio, Célia S. J. [UNESP] (2015)
Inflammatory fibroid polyp (IFP) is a benign uncommon lesion (1%-4% of gastric benign lesions), originated from the submucosa of the gastrointestinal tract. Its origin is controversial and immunohistochemical studies of lesions have largely refuted the possible vascular, neural or smooth muscle origin. Recent studies suggest a neoplastic etiology due to a mutation, in some cases, in the alpha-type platelet-derived growth factor receptor gene (PDGFRa). Our objective is to report the case of a patient aged 70 years, with gastric IFP, comparing her immunohistochemical profile with those of other studies, and a brief review of the literature.